UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA DENGAN MENGGUNAKAN METODE OUTDOOR LEARNING PADA PEMBELAJARAN IPAS KELAS IV DI SDN GLADAK ANYAR 4 - Shinta Oktafiana; Siska Arifah Ningsih; Siti Jumaatul Maylah; Arif Fuadi (EBTIDA': Jurnal Pendidikan Dasar Islam, 2023)
The research carried out aims to increase student learning motivation by using outdoor learning methods for class IV students at SDN Gladak Anyar 4 Pamekasan. This research uses the Classroom Action Research (PTK) method using the flow of action implementation by Kemmis and McTaggart. The subjects or participants in this research were class IV students at SDN Gladak Anyar 4 Pamekasan, totaling 31 people consisting of 18 boys and 13 girls as well as one colleague whose position was a research collaborator. The research was carried out through a pre-cycle stage and two cycles with each cycle consisting of two meetings and an estimated time of 2 x 35 minutes. Each cycle consists of planning, implementation, observation and reflection stages. The results of this research indicate an increase in student learning motivation by using the outdoor learning method in terms of observation indicators of teacher skills which reached a final gain of 91%, student activity which reached a final gain of 92%, and the use of outdoor learning methods reached a final gain of 94%. The research conclusion is that outdoor learning methods that are implemented well can increase student learning motivation in class IV students at SDN Gladak Anyar 4 Pamekasan.